2015
DOI: 10.4236/ojemd.2015.57010
|View full text |Cite
|
Sign up to set email alerts
|

Avocado and Cardiovascular Health

Abstract: Avocado is a fruit which had a caloric density of 1.7 kcal per gram and a half unit (~70 g) is composed by 114 kcal, 4.6 g of fibers, 345 mg of potassium, 19.5 mg of magnesium, 1.3 mg of vitamin E and 57 mg of phytosterols. Approximately 75% of fiber's avocado contents are considered insoluble and 25% are soluble. The avocado contains lipids that consist of 71% from monounsaturated fatty acids (MUFA), 13% from polyunsaturated (PUFA) and 16% from saturated fatty acids (SFA). Recent researches have shown that av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
(37 reference statements)
0
15
1
1
Order By: Relevance
“…The Mini-ECCA v.2 thus consists of 14 questions focused on assessing food and beverage (alcoholic and non-alcoholic) intake. The questions are based on a review of relevant literature on the subject, including Mexican [38,39] and international nutritional recommendations [1,35,36,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] (Table 1). For each question, three or four answer choices are given, generally on a Likert scale (see Table S1: Mini-ECCA v.2 survey).…”
Section: Modification Of the Mini-ecca Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…The Mini-ECCA v.2 thus consists of 14 questions focused on assessing food and beverage (alcoholic and non-alcoholic) intake. The questions are based on a review of relevant literature on the subject, including Mexican [38,39] and international nutritional recommendations [1,35,36,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] (Table 1). For each question, three or four answer choices are given, generally on a Likert scale (see Table S1: Mini-ECCA v.2 survey).…”
Section: Modification Of the Mini-ecca Questionnairementioning
confidence: 99%
“…It is recommended to consume 20-30 g of nuts, seeds and olives [41] due to the decrease in cardiovascular risk factors associated with their daily intake, and particularly in light of the antioxidant properties of this food group which may inhibit or delay atherogenic processes [42,43,58]. No precise avocado intake recommendations have been established, but a minimum intake of half of an avocado per day has been found to be effective in reducing cardiovascular risk [44,45].…”
Section: Oilseeds and Avocadomentioning
confidence: 99%
“…Recent investigations have shown that avocado may improve hypercholesterolemia and be useful in the treatment of hypertension and type 2 diabetes mellitus (Tabeshpour et al , ). Weschenfelder et al () reported that avocado consumption seems to be related to cardiometabolic health by preventing traditional risk factors such as dyslipidemia, glycemic control and hypertension. Few studies have discussed the mechanisms through which antioxidants (polyphenols, tocopherols, vitamins, carotenoids), MUFA, fibre and phytosterols exert such beneficial effects (Silva‐Caldas et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…[10] The fruit has long been used as a healthy food and recent researches have shown that avocado can improve hypercholesterolemia and be useful in the treatment of hypertension, in type 2 diabetes mellitus, hypertension, and dyslipidemia and can play an important role in cardiovascular health. [11,12] Avocado tissues are interesting natural sources of rich-phenolic extracts with high antioxidant and antimicrobial potential. [13] The lipophilic extract of avocado inhibits prostate cancer cell growth, [14] induces apoptosis in human breast cancer cells, [15] and suppresses liver injury.…”
Section: Introductionmentioning
confidence: 99%